Advances in Our Understanding of the Mechanism of Action of Drugs (including Traditional Chinese Medicines) for the Intervention and Treatment of Osteoporosis - Lu, Junjie; Hu, Desheng; Ma, Chen; Shuai, Bo (Frontiers in Pharmacology, 2022)
Osteoporosis (OP) is known as a silent disease in which the loss of bone mass and bone density does not cause obvious symptoms, resulting in insufficient treatment and preventive measures. The losses of bone mass and bone density become more severe over time and an only small percentage of patients are diagnosed when OP-related fractures occur. The high disability and mortality rates of OP-related fractures cause great psychological and physical damage and impose a heavy economic burden on individuals and society. Therefore, early intervention and treatment must be emphasized to achieve the overall goal of reducing the fracture risk. Anti-OP drugs are currently divided into three classes: antiresorptive agents, anabolic agents, and drugs with other mechanisms. In this review, research progress related to common anti-OP drugs in these three classes as well as targeted therapies is summarized to help researchers and clinicians understand their mechanisms of action and to promote pharmacological research and novel drug development.